2019
DOI: 10.11606/1807-0205/2019.59.18
|View full text |Cite
|
Sign up to set email alerts
|

Run to the nest: A parody on the Iron Maiden song by Corotoca spp. (Coleoptera, Staphylinidae)

Abstract: Rove beetles belonging to the genus Corotoca (Staphylinidae: Aleocharinae) are termitophiles exclusively found in nests of Constrictotermes (Isoptera: Termitidae). We observed the reproductive behavior of Corotoca melantho and C. fontesi during host (C. cyphergaster) foraging events. The reproductive behaviors of both species are similar. The variables collected for analysis were distance traveled, the time of larval deposition, nest return time, and locomotion speed. The fact that the female stops in the midd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
2
0
3
Order By: Relevance
“…We understand the importance of research with controlled variables, such as temperature and moisture, but nonetheless encourage more field observations that can be merged with laboratory observations. Studies carried out in the Cerrado areas demonstrated fewer field experiments than those carried out in the Caatinga domain, resulting in gaps in our knowledge in the Cerrado areas concerning interactions with termitophiles during foraging ( Figure 6 ) [ 40 , 41 ], lichen consumption ( Figure 7 ), the identification of the assemblage composition of the lichens consumed, and the possible relationships between lichens and nests [ 21 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…We understand the importance of research with controlled variables, such as temperature and moisture, but nonetheless encourage more field observations that can be merged with laboratory observations. Studies carried out in the Cerrado areas demonstrated fewer field experiments than those carried out in the Caatinga domain, resulting in gaps in our knowledge in the Cerrado areas concerning interactions with termitophiles during foraging ( Figure 6 ) [ 40 , 41 ], lichen consumption ( Figure 7 ), the identification of the assemblage composition of the lichens consumed, and the possible relationships between lichens and nests [ 21 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, leaving the nest could also ensure dispersal. After depositing the larvae, females return to the nest (Moreira et al, 2019).…”
Section: Model Species and Natural Historymentioning
confidence: 99%
“…Em estágios avançados do desenvolvimento observa-se uma larva desenvolvida no ápice do abdômen e dois ovos na base. Como essa larva é liberada e como a espécie se dispersa foi descrita primeiramente em Oliveira et al (2018), e explorada e discutida em mais detalhes em outros trabalhos (Moreira et al, 2019;Zilberman et al, 2019). Nesses estudos, foi visto que durante o forrageamento do hospedeiro Constrictotermes sp., a fêmea do besouro, pronta para liberar a prole, segue a trilha do cupim, caminha até um certo ponto, e então para, virando-se em 180 graus, tornando a ficar de frente contra o fluxo de operários que saem do ninho para forragear.…”
Section: Tribo Corotociniunclassified
“…O valor adaptativo de tal semelhança, contudo, pode não ser visto exclusivamente como mecanismo de integração com seus hospedeiros. Moreira et al (2019) A morfologia limulóide em Aleocharinae, é possivelmente uma adaptação para a vida embaixo de cascas de árvores e serrapilheira, que foi cooptada para resistir a agressões do hospedeiro Yamamoto et al, 2017). Apesar dessa forma sugerir a necessidade dos termitófilos se defenderem de seus hospedeiros, existem registros de contatos íntimos entre termitófilos limulóides e seus hospedeiros .…”
Section: Mimetismo Para Plano Corporalunclassified
See 1 more Smart Citation